Creative Economy as a Driver of Economic Growth in the Digitalization Era - Anandiya Pingki; eddy Silamat; Hernawati Hernawati; Rashid Rahman (Journal of Multidisciplinary Sustainability Asean, 2025)
Background. The creative economy has become one of the main sectors in the global economy, especially in the era of digitalization that allows the transformation of business models based on innovation and technology. The development of digital technology provides opportunities for creative industry players to expand market reach, improve production efficiency, and create greater added value. Countries with good digital infrastructure show more stable and competitive creative economy growth than countries with limited access to technology. Purpose. This study aims to analyze the role of digitalization in driving the growth of the creative economy and identify the factors that affect its success. In addition, this study also explores the contribution of the creative economy sector to the national economy by considering regulatory aspects and digital literacy. Method. The research method used is a quantitative approach with regression analysis and case studies on several creative economy sectors. Primary data is collected through surveys of creative industry players, while secondary data is obtained from official government reports and related academic publications. Results. The results show that digitalization has a significant influence on the growth of the creative economy, with the app and gaming sectors being the main examples of successful technology adoption. The creative economy sector, which is faster to adapt to digital technology, has experienced higher growth than sectors that still rely on conventional methods. Supportive regulations and a good level of digital literacy play an important role in ensuring the sustainability of the creative industry in the era of digitalization. Conclusion. The conclusion of this study emphasizes that the creative economy can be the main driver of economic growth if supported by the right policies and a conducive digital ecosystem. Digital transformation in the creative industry is not just a trend, but also a need to increase economic competitiveness on a global scale.